2008
DOI: 10.1159/000129388
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Inhibits LPS-Induced Signaling Pathways in Alveolar Macrophages

Abstract: The systemic inflammatory response syndrome (SIRS) is triggered by lipopolysaccharide (LPS) from Gram-negative bacteria. Insulin was shown to have a protective role in SIRS related to sepsis. Lungs are particularly affected in this condition and provide a second wave of mediators/cytokines which amplifies SIRS. The aim of the present study was to investigate the effect of insulin on the signaling pathways elicited by LPS in alveolar macrophages (AMs) and its consequence in cellular response to LPS measured as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 33 publications
(38 reference statements)
6
34
0
4
Order By: Relevance
“…It has recently been discussed extensively by Davies and Taylor [30], and by Perdiguero and Geissmann [31]. By acting on non-diabetic [27] and diabetic mononuclear cells [24], it has been demonstrated that insulin plays additional roles beyond glucose uptake [32] and seems to have important immunomodulatory effects in macrophages. Moreover, insulin binds to its own receptor and has different roles depending on the cell type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been discussed extensively by Davies and Taylor [30], and by Perdiguero and Geissmann [31]. By acting on non-diabetic [27] and diabetic mononuclear cells [24], it has been demonstrated that insulin plays additional roles beyond glucose uptake [32] and seems to have important immunomodulatory effects in macrophages. Moreover, insulin binds to its own receptor and has different roles depending on the cell type.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were treated at a final concentration of 1 mU/mL of insulin from bovine pancreas [27] (Sigma Chemical Co, St. Louis, Mo, USA) concomitantly stimulated with or without LPS (100 ng/mL) from Escherichia coli (serotype 055:B5) (Sigma Chemical Co, St. Louis, Mo, USA) for different time point in different assays. For the inhibition assay, BMDM from diabetic animals were pre-treated with inhibitors for PI3K (10 µM LY294002 and/or 10 nM wortmannin); ERK1/2 (2 µM PD98059) and/or p38 (10 µM SB20190) for 1 h before LPS and/or insulin addition [28].…”
Section: Methodsmentioning
confidence: 99%
“…Conflicting results about the effect of insulin on cytokine production in macrophages exist. Although insulin inhibited LPS-stimulated kinase activation and TNF␣ production in rat alveolar macrophages (17), it enhanced the LPS-elicited IL-1␣ and IL-1␤ release from whole blood of healthy male volunteers subjected to a hyperinsulinemic euglycemic or hyperinsulinemic hyperglycemic clamp for 6 h prior to blood collection (33). In a different study, the impact on cytokine production of insulin alone was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with reports in mammals because insulin regulates the inflammatory response either directly or indirectly. [65][66][67][68][69][70][71][72] As in the case of the lethal LPS treatment, the lipid metabolism-related genes were affected: the low-density lipoprotein receptor (LDLR) was the most up-modulated gene at 4 dpf. Because LPS can be bound by triglyceride-rich lipoproteins (TRL) that may be internalized through the LDLR pathway, the internalization of lipoprotein bound endotoxin (TRL-LPS) could attenuate the systemic inflammatory response.…”
Section: Dios Et Almentioning
confidence: 99%